Eolian Deposition and Soil Fertility in a Prehistoric Agricultural Complex in Central Arizona, USA. Issue 2 (5th February 2014) - Nakase, Dana K.; Hartshorn, Anthony S.; Spielmann, Katherine A.; Hall, Sharon J.
<x xml:space="preserve">Abstract</x> Prehistoric farmers in arid and semiarid ecosystems commonly used rock alignments to concentrate water and sediments on their fields. Previous research has emphasized the importance of runoff from organic matter‐rich uplands as a mechanism for soil nutrient replenishment. However, eolian inputs to these dryland ecosystems might also contribute substantially to mineral‐derived nutrient pools. We explored the relative importance of eolian deposition, prehistoric agriculture, and the presence of rock alignments on soil properties in a semiarid grassland in Arizona. Subsurface soils behind natural rock alignments are finer in texture than soils unbound by rock alignments, while subsurface soils behind agricultural rock alignments coarsen relative to unbound soils. Neither rock alignments nor estimated crop yields had detectable effects on mineral‐derived nutrient pools. In contrast, eolian deposition is an important source of soil mass and nutrients to modern soils. While dust deposition likely reduced soil heterogeneity across this landscape, it could have also contributed to the sustainability of prehistoric agriculture.